PENGGUNAAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MENGHITUNG LUAS TRAPESIUM DAN LAYANG-LAYANG DI KELAS V SD - KHAIRAT, VIRA ISMIS (Universitas Negeri Padang, 2014)
Abstract This research was designed for describing the improvement of the students’ learning achievement on the calculate area of trapezium and layang-layang by using Contextual Teaching and Learning approach in the fifth grade of SDN 34 Simpang Haru Kota Padang. The subject of the research was the teacher and 32 students’ of the school. The result of the research showed that there was an improvement on: the plan about 17,86%, on the teacher aspects about 18,5% and the students’ aspects for 16%, and the students’ learning achievement about 15,27. Kata Kunci : Luas trapesium dan layang-layang, CTL